The relationship between breastfeeding and reported respiratory and gastrointestinal infection rates in young children - Nicole M. Frank; Kristian F. Lynch; Ulla Uusitalo; Jimin Yang; Maria Lönnrot; Suvi M. Virtanen; Heikki Hyöty; Jill M. Norris; for the TEDDY Study Group (BMC, 2019)
Abstract Background Although breastfeeding is touted as providing many health benefits to infants, some aspects of this relationship remain poorly understood. Methods The Environmental Determinants of Diabetes in the Young (TEDDY) is a prospective longitudinal study that follows children from birth through childhood, and collects data on illness events, breastfeeding duration, and time to introduction of formula or foods at 3 month intervals up until 4 years of age and at 6 months intervals thereafter. Exclusive and non-exclusive breastfeeding is examined in relation to the 3-month odds of a respiratory or gastrointestinal infection for 6861 children between the ages of 3-18 months, and 5666 children up to the age of 4 years. Analysis was performed using logistic regression models with generalized estimating equation methodology. All models were adjusted for potential confounding variables. Results At 3-6 months of age, breastfeeding was found to be inversely associated with the odds of respiratory infections with fever (OR = 0.82, 95% CI = 0.70-0.95), otitis media (OR = 0.76, 95% CI = 0.62-0.94), and infective gastroenteritis (OR = 0.55, 95% CI = 0.46-0.70), although the inverse association with respiratory illnesses was observed only for girls during the winter months. Between 6 and 18 months of age, breastfeeding within any 3 month period continued to be inversely associated with the odds of ear infection and infective gastroenteritis, and additionally with the odds of conjunctivitis, and laryngitis and tracheitis, over the same 3 month period within this age range. However, breastfeeding in this group was associated with increased reports of common cold. Duration of exclusive breastfeeding was inversely associated with the odds of otitis media up to 48 months of age (OR = 0.97, 95% CI = 0.95-0.99) after breastfeeding had stopped. Conclusions This study demonstrates that breastfeeding can be protective against multiple respiratory and gastrointestinal acute illnesses in some children up to at least 6 months of age, with duration of exclusive breastfeeding being somewhat protective of otitis media even after breastfeeding has stopped. Trial registration ClinicalTrials.gov Identifier: NCT00279318. Date of registration: January 17, 2006 (proactively registered). First Posted: January 19, 2006.